Impact of Reciever on Time on the Energy Saving Performance of the Watchful Sleep Mode in a Passive Optical Network - .M. Zin, A; M. Idrus, S; A. Butt, Rizwan; Ramli, A (International Journal of Engineering and Technology, 2018)
Due to increasing bandwidth demands from users, this evolution towards next generation PON (NG-PON) with higher network capacity and split continues. However, increasing split ratio in NGPON also leads to higher power consumption of the PON network due to 60% of the power is being consumed by the optical network units (ONUs). For energy conservation of the ONU, the Watchful Sleep Mode (WSM) has been recently added to the PON standards. This is an integrated mode that combines both the cyclic sleep and doze mode in one operation by periodically turning on the ONU receiver (RX) during the sleep cycle. However, still, the impact of RX on time on the energy saving performance of WSM has not been studied. Therefore, this study presents a performance evaluation of the watchful sleep mode in a 10 GB-capable PON (XG-PON) network with varying RX ON times. The investigation is performed with a dynamic bandwidth assignment scheme and real traffic data from Broadcom CATV head end. A comprehensive review of the power saving techniques for XGPON is also presented. The simulation study results show that higher RX ON time leads to higher energy savings for the ONUs without significantly increasing upstream and downstream delays.Â Â